Large Eddy Simulation of Film Cooling with Bulk Flow Pulsation: Comparative Study of LES and RANS - Seung Il Baek; Joon Ahn (Applied Sciences, 2020)
The effects of bulk flow pulsations on film cooling in gas turbine blades were investigated by conducting large eddy simulation (LES) and Reynolds-averaged Navier–Stokes simulation (RANS). The film cooling flow fields under 32 Hz pulsation in the mainstream from a cylindrical hole inclined 35° to a flat plate at the average blowing ratio of M = 0.5 were numerically simulated. The LES results were compared to the experimental data of Seo, Lee, and Ligrani (1998) and Jung, Lee, and Ligrani (2001). The credibility of the LES results relative to the experimental data was demonstrated through a comparison of the time-averaged adiabatic film cooling effectiveness, time- and phase-averaged temperature contours, Q-criterion contours, time-averaged velocity profiles, and time- and phase-averaged Urms profiles with the corresponding RANS results. The adiabatic film cooling effectiveness predicted using LES agreed well with the experimental data, whereas RANS highly overpredicted the centerline effectiveness. RANS could not properly predict the injectant topology change in the streamwise normal plane, but LES reproduced it properly. In the case of the injectant trajectory, which greatly influences film cooling effectiveness, RANS could not properly predict the changes in the streamwise velocity peak due to flow pulsation, but they were predicted well with LES. RANS greatly underpredicted the streamwise velocity fluctuations, which determine the mixing of main flow and injectant, whereas LES prediction was close to the experimental data.